Enhancing agricultural production and productivity in Uganda through irrigation - Mwaura, Francis; Katunze, Miriam (Economic Policy Research Centre, 2014)
Although Uganda has a high agricultural potential due to its favourable climatic and soil characteristicsi, frequent episodes of droughts and famine have affected agricultural yields. Indeed, recent droughts have been associated with decline and in some instances stagnation of the country’s agricultural productionii. In this policy brief, we examine Uganda’s prospects for enhancing agricultural productivity through irrigation.